Nasendoscopy for unusual nasal symptoms. (10th September 2010) - Vedasalam, S; Sipaul, F; Hill, A; Porter, G
Abstract : A 20-year-old woman who was fit and well presented with a history of left nasal blockage for 2 years. She was noted on anterior rhinoscopy to have nasal septal deviation towards the left. She was listed for septoplasty with the aim of relieving nasal obstruction. At operation she was found to have a mildly deviated septum to the left. There was also a rhinolith in the left nostril posterior to the deviated septum (figure 1 ). Following removal of the rhinolith, her nasal airway appeared adequate; hence, septoplasty was not performed. Postoperatively, the patient was pleased with the outcome. When the patient was shown the foreign body she recalled inserting a pen cover into her nose about 10 years previously (figure 2 ). When she presented to the Accident and Emergency department at that time she was told that there was no foreign body in her nose.